Does the NHS Diabetes Prevention Programme prevent diabetes? A population-based matched cohort study. (30th September 2020) - Nguyen, V; Aldridge, R; Blackburn, R; Hayward, A; Greaves, F; Flowers, J
Abstract: Background: To reduce the incidence of type 2 diabetes (T2DM) in England, the National Health Service piloted the Diabetes Prevention Programme (DPP). The DPP aims to prevent T2DM by providing high-risk adults with access to 13 face-to-face sessions over nine months that focus on diet and weight management. The DPP has been shown to improve intermediate outcomes for T2DM prevention (weight loss and glycated haemoglobin (HbA1c) reduction). However, there is a lack of evidence examining incident T2DM as the outcome. Methods: We conducted a retrospective observational cohort study using linked electronic health records from primary (Clinical Practice Research Datalink) and secondary (Hospital Episode Statistics) care for June 2016 to January 2019. We compared rates of new T2DM diagnoses among eligible adults who were referred to the DPP with rates for propensity score-matched (ratio of 1:4) controls who were eligible for the DPP but were not invited. DPP eligibility was defined as having HbA1c levels of 42-47 mmol/mol or fasting plasma glucose (FPG) levels of 5.5-6.9 mmol/L. Adults with pre-existing T2DM were excluded. Time to the first record of T2DM was modelled using Cox regression with age, alcohol intake, body mass index, ethnicity, sex, HbA1c, index of multiple deprivation and smoking status included as covariates. Results: We identified 2205 individuals who participated in the DPP and 8820 matched controls with a similar breakdown in age, sex, HbA1c and FPG. During the 2.5-year study period, 4.13% of DPP individuals developed T2DM vs 6.42% of controls. Our results indicate that DPP referrals were associated with a 59% reduction T2DM incidence rates [adjusted hazard ratio=0.41;95%CI=0.38-0.44]. Conclusions: This is the first study to investigate the impact of the DPP on T2DM, relative to usual care. Our results provide support for the effectiveness of DPP in preventing T2DM onset and are compatible with findings for similar interventions in other settings. Key messages: The evidence suggests that providing consistent face-to-face sessions which concentrate on diet and weight management can reduce short-term T2DM incidences in high-risk adults. With a 59% reduction in T2DM rates in DPP referees relative to eligible adults who were not referred, the DPP is effective in reducing short-term T2DM incidences in high-risk adults.